ANALISIS FINANSIAL USAHA PETERNAKAN BABI CV. RINDRILLY DI DESA TONTALETE KECAMATAN KEMA KABUPATEN MINAHASA UTARA - Manampiring, Selina P; Lumy, T F.D; Pangemanan, S P; Lumenta, I D.R (Universitas Sam Ratulangi, 2020)
FINANCIAL ANALYSIS OF THE CV. RINDRILLY SWINE FARM AT TONTALETE VILLAGE, KEMA DISTRICT OF NORTH MINAHASA REGENCY. The CV. Rindrilly Swine Farm has been established in the year of 2000. The objective of this study was to evaluate the financial feasibility of CV. Rindrilly Swine Farm. Case study method was applied in this study. The primary data were obtained by interviewing directly to the owner of the pig farm using listed questioners. The secondary data were found from the â€œBadan Pusat Statistik (BPS)â€ of North Minahasa regency and other research reports related to this study. Descriptive analysis and investment criteria analysis were used in this study. Results of this study showed that the financial aspect was feasible in term of investment criteria appraisal including BEP unit with 288 heads of pig per period of production and BEP in IDR amount IDR 807,437,525.- per period of production. These criteria was reaching the break event point due to the total animals sold were 1,500 heads per period of production during 6 months with the total IDR output of 8,869,000,000 per year. The values of Net B/CÂ and Gross B/C Â equal to 1.18 and 1.26, respectively. The value of NPV equal to IDR 764,420,240.- and IRR value equal to 22.18 percents > bank interest rates.